Diagnostic utility of point of care ultrasound in identifying cervical spine injury in emergency settings. Issue 4 (2nd July 2021) - VK, Vishnu; Bhoi, Sanjeev; Aggarwal, Praveen; Murmu, LR; Agrawal, Deepak; Kumar, Atin; Sinha, Tej Prakash; Galwankar, Sagar
Abstract: Introduction: The evaluation of cervical‐spine in a major trauma patient needs a bedside efficient tool to rule out cervical spine injury as the role of X‐ray and Computed Tomography (CT) in this setting is limited. Point of care ultrasonography (POCUS) is being used as an adjunct during trauma resuscitation. The aim of this study was to evaluate the use of POCUS for identifying cervical spine injuries. Methods: We recruited 84 cases with cervical spine injury based on CT scan after taking consent. POCUS was used as per the operational definition of study methods while maintaining manual in‐line stabilisation. Statistical analysis was done by using STATA version 14. Results: Normal cervical anatomy was visible through anterior approach in POCUS except for the 1 st and 2 nd cervical vertebrae. The sensitivity and specificity of POCUS vs CT scan for vertebral body listhesis were 84.52% (95% CI of 0.65–0.95) and 89.66% (95% CI 0.78–0.96) with p ‐value <0.0001. Sensitivity and specificity of POCUS vs CT for vertebral body fracture were 40.91% (95% CI of 0.20–0.63) and 96.77% (95% CI of 0.88–0.99) with p ‐value <0.0001. The overall sensitivity and specificity of POCUS were 45.83% and 83.33% ( p = 0.06) and excluding isolated posterior column injuries, sensitivity and specificity were 70.21% and 83.33% ( p < 0.05). Conclusion: POCUS identified injuries such as fracture and listhesis. Because of high rate of missed injuries, ultrasound at present cannot be used as a screening or diagnostic tool for decision‐making in cervical spine injury.